La fête éclatée : un nouveau type de fête locale ? - Anne-Laure Briand; Laurent Sébastien Fournier; Ghislaine Gallenga; Éric Pons (Socio-anthropologie, 2018)
The article documents the renewal of local festivals and their changes in a world more and more influenced by individualism and by the notion of leisure. It suggests that a new type of local festival, “fragmented festivals”, is now superimposed to well known “traditional” and “revitalized” festivals. This new type of festival is typical because it combines a dispersion of the audience and a fragmentation in the local space of the activities proposed to him. Ethnographic fieldwork in the cherry market festival in La Roque-d’Anthéron (Bouches-du-Rhône district, Provence) questions the actual transformations of local festivals and their connection with more general transformations of contemporary societies.